Monetary Policy in the United States Under Flexible Exchange Rates - Papell, David H. (American Economic Review, 1989)
This paper estimates and evaluates monetary policy rules within the context of a structural open economy macroeconomic model of the United States under flexible exchange rates. The major result is that a monetary policy rule which stabilizes the rate of growth of nominal GNP receives considerable empirical support. The rule provides a better fit than a number of alternatives, including strict inflation stability, strict output stability, and real exchange rate stabilization.